A molecular analysis of the armadillo Dasypus novemcinctus (Mammalia: Dasypodidae), one of the most common victim of poaching in America. (December 2017) - Machado, J.C.A.; Silva, D.A.; Amorim, A.; Gallo, V.; Geise, L.; Carvalho, E.F.; Amaral, C.R.L.
Abstract: One of the taxa suffering from intense poaching activities along its entire occurrence area, Dasypus represents a genus of armadillos that comprises seven living species: D. hybridus, D. kappleri, D. novemcinctus, D. pilosus, D. sabanicola, D. septemcinctus, and D. yepesi . The aim of this study is to analyze the genetic diversity of D. novemcinctus in order to build a haplotype database for molecular identification purposes. Molecular analyses were performed using the database that includes 99 sequences with 762 bp of the mitochondrial gene Cytochrome b of D. novemcinctus from several localities including North, Central and South America. We performed a maximum likelihood analysis and constructed a median-joining network using the Geneious and PopART softwares respectively. Sequences of the remaining Dasypus species and other armadillos were also included for the molecular analyses. The obtained results suggest four distinct lineages (groups I, II, III and IV) among D. novemcinctus haplotypes. Group I was the largest, with 53 haplotypes and spread over Brazil, Paraguay and Peru. The results reinforced the use of the genetic marker Cytochrome b as an effective tool in the identification of D. novemcinctus .